Board Characteristics and Research and Development of Listed Manufacturing Firms in Nigeria - Wisdom, Okere; Grace, Offiaeli Amarachuwku; Stephanie, Ilo (Asian Journal of Empirical Research, 2022)
The study evaluated the impact of board characteristics on the research and development of quoted manufacturing firms in Nigeria. Its objective was to assess the association between board characteristics and R&D in quoted manufacturing firms in Nigeria. The scope of the study was from 2011 to 2020, secondary data was adopted in this study, which was extracted from the corporate reports of the listed food-manufacturing firms in Nigeria. The study made use of a sample size of 10 manufacturing firms. The agency theory was adopted in the work. A panel ordinary least square regression was used to test for the relationship and impact of the variable and the results. The findings of the study show a positive correlation between board characteristics and R&D in listed food manufacturing firms in Nigeria. This study recommends that the manufacturing firms should not overlook the effect research and development have on the value creation of the firms as over time this would promote business sustainability.